2003
DOI: 10.1002/j.2050-0416.2003.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of a Protease from Sorghum Malt Variety KSV8-11

Abstract: A protease from sorghum malt variety KSV8-11 was purified by a combination of dialysis against 4 M sucrose, ion-exchange chromatography on Q-Sepharose (Fast flow), gel filtration chromatography on Sephadex G-100 and hydrophobic interaction chromatography on Phenyl Sepharose CL-4B. The enzyme was purified 5-fold to give a 14.1% yield relative to the total activity in the crude extract and a final specific activity of 1348.9 U mg -1 protein. SDS-PAGE revealed a single migrating protein band corresponding to a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
(28 reference statements)
3
17
0
Order By: Relevance
“…Malts from all the sorghum lines showed more in-gel proteinase activity and bands than their respective ungerminated grains, confirming earlier reports (Evans and Taylor 1990;Ogbonna et al 2003) of substantial increases in proteinase activity during germination. Increase in proteinase activity during malting could have been due both to the emergence of new isozyme forms as well as increase in the activity of isozymes already present in the ungerminated seeds.…”
Section: Electrophoretic Separation Of Sorghum Malt Proteinasessupporting
confidence: 88%
See 1 more Smart Citation
“…Malts from all the sorghum lines showed more in-gel proteinase activity and bands than their respective ungerminated grains, confirming earlier reports (Evans and Taylor 1990;Ogbonna et al 2003) of substantial increases in proteinase activity during germination. Increase in proteinase activity during malting could have been due both to the emergence of new isozyme forms as well as increase in the activity of isozymes already present in the ungerminated seeds.…”
Section: Electrophoretic Separation Of Sorghum Malt Proteinasessupporting
confidence: 88%
“…Indeed in an earlier study, Ogbonna et al (2003) had purified a cysteinetype proteinase from malts of an improved Nigerian sorghum cultivar that was stimulated 11-41% by the divalent cations Zn 2+ , Cu 2+ , and Sr 2+ . Indeed in an earlier study, Ogbonna et al (2003) had purified a cysteinetype proteinase from malts of an improved Nigerian sorghum cultivar that was stimulated 11-41% by the divalent cations Zn 2+ , Cu 2+ , and Sr 2+ .…”
Section: Effects Of Exogenous Proteinase-class Inhibitorsmentioning
confidence: 99%
“…Timotijević et al 2 purified three forms of 47, 40 and 28 kDa aspartic proteases from mature buckwheat seeds. In sorghum malt an acidic protease with an optimal pH of 5.0 was purified from variety KSV8‐11,3 while a neutral protease with an optimal pH of 6.0 was purified from variety SK5912 4. Both were inhibited by iodoacetic acid and p ‐chloromercuribenzoate.…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum malt variety KSV8 contains two distinct proteases separated by gel filtration chromatography on Sephadex G-100, purified and characterised as KSV8-11 with a lower relative molecular weight as reported in our earlier communications (Ogbonna et al 2003), while KSV8-I with a higher relative molecular weight is reported in this paper. pH % Relative activity Stability Activity Figure 6.…”
Section: Resultsmentioning
confidence: 77%
“…Sorghum variety (KSV8)/germination; enzyme extraction/assay; protein estimation; enzyme purification protocols using 4 M sucrose solution, ion-exchange chromatography on Q-and S-Sepharose, gel filtration chromatography on Sephadex G-100 and hydrophobic interaction chromatography on phenyl-Sepharose CL-4B; molecular properties using SDS-PAGE; physicochemical and catalytic properties of the purified enzyme using standard/international methods were carried out as detailed in our earlier communications (Ogbonna et al 2003(Ogbonna et al , 2004.…”
Section: Methodsmentioning
confidence: 99%